Analisis Quality of Service Video Conference Berbasis Web pada Jaringan VPN Menggunakan Telkom Speedy - Rafael A.G.Soares; Fitro Nur Hakim (LPPM Politeknik Pratama Kendal, 2021)
Telkom Speedy is one of the companies engaged in the field of internet services. In the tight competition to attract and retain customers make Telkom Speedy need to know the level of customer satisfaction with the services provided by Telkom Speedy Internet in meeting the needs of Internet users as send and receive data, share information to conduct face-to-face through virtual worlds such as video conference that uses internet access. This study aims to analyze the Quality of Service on the Web-based video conferencing services using Telkom Speedy pass VPN network in order to know the performance and quality of video conferencing using the services of Telkom Speedy. The parameters used are Delay, Packet Loss, and Throughput